Proceedings of the 3rd ACM/IEEE International Conference on Human Robot Interaction 2008
DOI: 10.1145/1349822.1349843
|View full text |Cite
|
Sign up to set email alerts
|

How quickly should communication robots respond?

Abstract: Time Figure 1: Robot performs conversational fillers to buy time That one! Oh, this one. OK, I'll bring it later.etto... This paper reports a study about system response time (SRT) in communication robots that utilize human-like social features, such as anthropomorphic appearance and conversation in natural language. Our research purpose established a design guideline for SRT in communication robots. The first experiment observed user preferences toward different SRTs in interaction with a robot. In other exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…There are a variety of tools available for HRI researchers seeking to assess aspects of the societal acceptance of robots [48,131]. From most past researchers done to assess the societal acceptance of robots, there include: (1) ethnographic observation [38], (2) system response-time analysis [153], (3) common ground analysis [161], (4) embodiment measurement [29], (5) perceived enjoyment analysis [59], (6) comfort level analysis [95], (7) interaction profile analysis [133], and others [48,131]. For people to accept robots in social contexts, it is important Fig.10(a).…”
Section: Social Acceptance Modelling For Hrimentioning
confidence: 99%
See 1 more Smart Citation
“…There are a variety of tools available for HRI researchers seeking to assess aspects of the societal acceptance of robots [48,131]. From most past researchers done to assess the societal acceptance of robots, there include: (1) ethnographic observation [38], (2) system response-time analysis [153], (3) common ground analysis [161], (4) embodiment measurement [29], (5) perceived enjoyment analysis [59], (6) comfort level analysis [95], (7) interaction profile analysis [133], and others [48,131]. For people to accept robots in social contexts, it is important Fig.10(a).…”
Section: Social Acceptance Modelling For Hrimentioning
confidence: 99%
“…This needs a type of modelling, which is always known as the Technology Acceptance Modelling (TAM) [20,21,23,55,57,61,63,135]. Nowadays, significant increase in the elderly population and the increased shortage of labour, as well as the explosion of costs in our daily expenses, have posed extreme challenges to our society [55,61,63,152]. However, how many research projects can explore the applicability of technological advances such as Intelligent Systems that enable people to live independently?…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the length of natural pauses in human dialogue ranges from 0.62 to 0.77 s [37], and that delays longer than 2 s during human-robot interaction make people feel frustrated [38]. In teleoperation, an operator requires time to search through content or type utterances, so it can be difficult to respond so quickly [39].…”
Section: Reaction Timementioning
confidence: 99%
“…When the operator is slow in choosing or typing a behavior, the system helps to fill the delay by automatically inserting conversational fillers such as "hmm…" or "please wait a moment" to avoid awkward silences [38]. Details about our implementation of this feature are explained in Sect.…”
Section: Automatic Fillersmentioning
confidence: 99%
“…We believe that a conversational filler behavior is useful to reduce such negative feelings [29]. In Japanese "etto" is used to buy time and resembles "well.…”
Section: Response Timing Of the Robot In Conversationsmentioning
confidence: 99%